Implementation of Contextual Approach Based on Questioning in Biology Learning on Human Movement Material at MTs Assyafi’iyah NW Penangsak - Yusup, Muh.; Sakdiah, Lailatul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study aims to explore the implementation of a contextual approach based on questioning in biology learning on human movement material at MTs Assyafi’iyah NW Penangsak. The research employs a qualitative descriptive method to gain an in-depth understanding of how the approach influences students' learning experiences. Data collection techniques include observations, interviews, and documentation to obtain comprehensive insights into the teaching and learning process. The collected data is analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the contextual approach based on questioning enhances students' engagement and comprehension of the subject matter. Teachers guide students to connect biological concepts with real-life contexts, encouraging critical thinking and active participation. The questioning strategy helps students construct knowledge effectively, improving their problem-solving abilities. Additionally, students demonstrate higher retention and motivation when learning through this approach. The study concludes that implementing a contextual approach based on questioning is effective in facilitating meaningful learning experiences in biology. It provides opportunities for students to relate theoretical knowledge to practical situations, leading to better understanding and academic performance. The implications suggest that teachers should incorporate questioning techniques within contextual learning strategies to foster deeper student engagement and comprehension. Future research could explore the effectiveness of this approach in different subjects and educational settings.